Cellular homeostatic tension and force transmission measured in human engineered tendon. (10th September 2018) - Giannopoulos, Antonis; Svensson, Rene B.; Heinemeier, Katja M.; Schjerling, Peter; Kadler, Karl E.; Holmes, David F.; Kjaer, Michael; Magnusson, S. Peter
Abstract: Tendons transmit contractile muscular force to bone to produce movement, and it is believed cells can generate endogenous forces on the extracellular matrix to maintain tissue homeostasis. However, little is known about the direct mechanical measurement of cell-matrix interaction in cell-generated human tendon constructs. In this study we examined if cell-generated force could be detected and quantified in engineered human tendon constructs, and if glycosaminoglycans (GAGs) contribute to tendon force transmission. Following de-tensioning of the tendon constructs it was possible to quantify an endogenous re-tensioning. Further, it was demonstrated that the endogenous re-tensioning response was markedly blunted after interference with the cytoskeleton (inhibiting non-muscle myosin-dependent cell contraction by blebbistatin), which confirmed that re-tensioning was cell generated. When the constructs were elongated and held at a constant length a stress relaxation response was quantified, and removing 27% of the GAG content of tendon did not alter the relaxation behavior, which indicates that GAGs do not play a meaningful role in force transmission within this system.